The Labyrinth of Leadership: Ibu Nyai’s Role in Islamic Psycho-Spiritual Pedagogy through Living Shalawat Nariyah - Nurul Azizeh; Abdul Basid; Muhammad Asnawi Sabil; Kholil Imam (DAAR EL-MAKRIFAH: Journal of Islamic Religious Education, 2026)
The dynamics of leadership in Indonesian pesantren continue to evolve amid modernization and patriarchal cultural structures that often limit women’s authority in religious and educational spaces. In this context, Ibu Nyai plays a strategic role as a spiritual leader, educator, and social mediator within pesantren communities. However, existing studies on pesantren leadership have largely focused on male religious authority, while the psycho-spiritual pedagogical role of Ibu Nyai through local Islamic traditions remains underexplored. This study aims to analyze the labyrinth of leadership experienced by Ibu Nyai in implementing Islamic psycho-spiritual pedagogy through the tradition of Living Shalawat Nariyah in Indonesian pesantren. This study employs a qualitative literature-based approach by analyzing classical Islamic texts, contemporary books, and reputable journal articles related to female leadership, psycho-spiritual pedagogy, and pesantren traditions published between 2020 and 2025. Data were analyzed using thematic analysis and conceptual interpretation. The findings reveal that Living Shalawat Nariyah functions not only as a religious ritual but also as a psycho-spiritual pedagogical medium that strengthens emotional resilience, spiritual awareness, and social harmony within pesantren communities. The study contributes to Islamic education discourse by offering a contextual framework for understanding female spiritual leadership in Indonesian pesantren.